Implementasi Model Project Based Learning Dalam Meningkatkan Motivasi Belajar Siswa-Siswi Kelas IX Di SMP Nurul Islam - Uswatun Hasanah; Ribut Prastiwi Sriwijayanti; Diana Muniro (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The difficulties of class IX students in understanding the subject matter at the Nurul Islam Junior High School can reduce learning motivation when learning time in class and assignments are given by teacher. In this case, it is caused by the school environment, the friends itself, bored feeling, personal and family problems, and the setting of rest time is the trigger too. So, increasing learning motivation of students in class IX need something new namely implementing the Project Based Learning model. The model is expected to be a solution to the student for understanding the subject matter, do not feel bored or bored in learning, active during learning and practicing independence in class. The method that is used is descriptive qualitative by describing the data in the form of narrative and detail based on facts in the field. The results of this study are the implementation of the Project Based Learning model with the results that is game "Snakes and Ladders" effective in increasing the learning motivation and understanding of class IX students, this is proven when students can explain the subject matter properly, are active and enthusiastic when playing the game.